Analytical Techniques for Studying the Physical Properties of Lipid Emulsions - Herrera, Maria Lidia (SpringerBriefs in Food, Health, and Nutrition, 2012)
Analytical Techniques for Studying the Physical Properties of Lipid Emulsions.